Simple and exact Monte Carlo algorithm for modelling of complex polymerization processes - Sosnowski, S. (Polimery, 2011)
A new, exact Monte Carlo algorithm for the simulation of living/controlled polymerization processes is proposed. In the algorithm macromolecules are represented by doubly linked lists, which are natural models of macromolecules. It allows modelling of elementary reactions by forming/breaking of links in the doubly linked list. As a result the algorithm has a very simple structure and high efficiency. All details of the modeled system: kinetics, molecular weight distributions, microstructure of macromolecules, etc., are accessible at any moment of simulation. Practical aspects of implementation of the new algorithm were emphasized: data structures, flowcharts, and source codes (Pascal).